Науковий стиль банківських текстів: ознаки норми та інновації - Зеніна, Анастасія; Zenina, Anastasiya (Східноєвропейський національний університет імені Лесі Українки, 2015)
Розмежовано засадничі ознаки банківського терміна; прокоментовано погляди вчених на явища багатозначності і метафоричності в галузевих термінологіях. Схарактеризовано специфіку трьох напрямків розвитку сучасної термінології банківської справи в період модернізації й оновлення її словника. The article dwells upon the analysis of the normative and innovation features of the scientific style of banking. The fundamental characteristics of banking term are marked, including the consistency, monosemy, no synonyms or antonyms, stylistic neutrality. The views of scientists on the phenomenon of polysemy and metaphor in industry terminology are commented. The specific features of the three basic directions in the development of modern Ukrainian terminology of banking in the period of modernization and renewal of its composition are studied. The nature of dynamic processes in the banking dictionary depends on extralinguistic factors due to changes in the system of the banking sector of the economy. Internationality terminology is supported by the new English borrowing. The native and borrowing terms produce derivatives based upon the native derivative models. The banking terminology use expressive units as a source of additional nomination forms, which are fixed with special dictionaries.
The Scientific Style of Banking: Signs of Standards and Innovation
Keywords: багатозначність; банківська справа; метафора; науковий стиль; термін; період; banking; metaphor; period; scientific style; term; polysemy